Mucosal prolapse in the pathogenesis of Peutz-Jeghers polyposis. Issue 1 (12th December 2005) - Jansen, M; de Leng, W W J; Baas, A F; Myoshi, H; Mathus-Vliegen, L; Taketo, M M; Clevers, H; Giardiello, F M; Offerhaus, G J A
Abstract : Germline mutations in LKB1 cause the rare cancer prone disorder Peutz-Jeghers syndrome (PJS). Gastrointestinal hamartomatous polyps constitute the major phenotypic trait in PJS. Hamartomatous polyps arising in PJS patients are generally considered to lack premalignant potential although rare neoplastic changes in these polyps and an increased gastrointestinal cancer risk in PJS are well documented. These conflicting observations are resolved in the current hypothesis by providing a unifying explanation for these contrasting features of PJS polyposis. We postulate that a genetic predisposition to epithelial prolapse underlies the formation of the polyps associated with PJS. Conventional sporadic adenomas arising in PJS patients will similarly show mucosal prolapse and carry the associated histological features.